CEO and board chair roles: To split or not to split? - Dey, Aiyesha; Engel, Ellen; Liu, Xiaohui (Journal of Corporate Finance, 2011)
We examine the performance and compensation implications of firms' decisions to combine the roles of CEO and board chairman (duality). We document that firms that split the CEO and chairman positions due to investor pressure have significantly lower announcement returns and subsequent performance, and lower contributions of investments to shareholder wealth. Further, these performance outcomes are more negative for firms with higher predicted probabilities of duality based on a model of economic determinants of board leadership structure. We also find that pay-performance sensitivity in CEO compensation contracts are significantly lower following a split in the CEO and chairman positions, and significantly higher following a combination in these positions. Our evidence suggests that on average, board leadership choices by firms and market responses are consistent with efficiency arguments, and recent proposals for all firms to separate the CEO and chairman roles warrant more careful consideration.